(untitled) (London Journal of Research In Management & Business, 2025)
This research examined the intricate relationship between cybersecurity threats and financial inclusion in Nigeria, providing novel insights into their dynamic interplay. Considering the staggering growth of cyber frauds targeting financial inclusion drivers in Nigeria, it has become critical to understand the impact of cybersecurity threats on financial inclusion, as inclusive finance is paramount for fostering comprehensive economic development. This study examined the relationship between cybersecurity threats and the demand/supply sides of financial inclusion. The data used were sourced from reputable institutions like the Nigeria Electronic Fraud Forum (NeFF) and the World Bank Development Indicator. The hypotheses of the study were robustly tested using three estimation techniques, which include Ordinary Least Squares (OLS), Two-Stage Least Squares (2SLS), and Generalized Method of Moments (GMM). Key findings challenged conventional wisdom, revealing unexpected relationships between cybersecurity threats and financial inclusion. Contrary to prior assumptions, a positive long-run relationship is revealed between cybersecurity threats and the demand side of financial inclusion. Additionally, cybersecurity threat has a significant influence on the supply side of financial inclusion. The study thus recommended a revised, robust, and innovative cybersecurity framework for the Nigerian financial sector. It also suggested a review of the theory of production to validly include digital/financial technology as the latest (fifth) factor of production to enable academia, practitioners, and indeed all other stakeholders to understand its features, merits, and demerits, and therefore be able to combat its inherent risks safely.